Enhanced Red Bellied Malimbe Swarm and Phlebia Radiata Optimization Algorithms for Active Power Loss Diminution in Transmission Network - Kanagasabai, Lenin (IEEE transactions on industry applications, 2024)
Enhanced Red Bellied Malimbe Swarm (ECO) algorithm and Phlebia radiata optimization (PRO) algorithm are applied to solve the Active Power loss diminution problem. Main objectives are active power loss diminution, voltage deviation minimization and voltage stability expansion. In Enhanced Red Bellied Malimbe Swarm (ECO) algorithm, natural actions of Chelicerata are integrated with Red Bellied Malimbe Swarm and differential mutation incorporated. Phlebia radiata optimization (PRO) algorithm is designed by imitating the search activities of Phlebia radiata for potential sustenance. In the initial segment design of the projected PRO algorithm, Phlebia radiata depend on the scent in the air to quest for sustenance springs is mathematically formulated. In the procedure local examination phase is employed in order to augment the exploitation capability. Validity of ECO algorithm and PRO algorithm is verified in 23 benchmark functions and IEEE30, 57 bus systems. Obtained values of active power loss diminution, voltage deviation minimization and voltage stability expansion are : IEEE 30 bus system- ECO; Active power loss -4.4432 (MW), voltage deviation minimization- 0.0801 (PU), voltage stability expansion - 0.1592 (PU). IEEE 30 bus system - PRO; Active power loss-4.4464 (MW), voltage deviation minimization- 0.0810 (PU), voltage stability expansion - 0.1589 (PU). IEEE 57 bus system - ECO; Active power loss-20.08(MW), voltage deviation minimization- 0.6009 (PU), voltage stability expansion - 0.2892 (PU). IEEE 57 bus system - PRO; Active power loss-20.19 (MW), voltage deviation minimization- 0.6012 (PU), voltage stability expansion - 0.2875 (PU). Active power loss diminution, voltage deviation minimization and voltage stability expansion are attained.